Analisis Trust Pada Parfum Isi Ulang di Toko Bima Wangi Kota Bima - Ridwan Ridwan; Irma Mardian (Journal of Business and Economics Research (JBE), 2020)
This study aims to determine the value of the independent variable, either one or more (independent) variables without making comparisons, or connecting with other variables. The sample used in the study was 96 respondents. From the results of the study, it was found that the level of consumer confidence in refill perfume at the Bima Wangi Store in Bima City was more than 75% or was good